Tubridge flow diverter for the treatment of small and medium aneurysms - Xie, Dajiang; Yang, Heng; Zhao, Li; Ye, Xin; Yang, Shuxu; Gao, Chao; Tian, Yanlong; Ni, Wei; Gu, Yuxiang (Frontiers in Neurology, 2023)
Background Tubridge flow diverter is a widely used device aimed at reconstructing parent arteries and occluding complex aneurysms in China. The experience of Tubridge in treating small and medium aneurysms is still limited. In this study, we aimed to evaluate the safety and efficacy of the Tubridge flow diverter for the treatment of the two types of aneurysms. Methods We reviewed the clinical records of aneurysms treated with a Tubridge flow diverter between 2018 and 2021 in a national cerebrovascular disease center. Cases were divided into small and medium aneurysms according to aneurysm size. The therapeutic process, occlusion rate, and clinical outcome were compared. Results In total, 57 patients and 77 aneurysms were identified. The patients were divided into two groups: small aneurysms (39 patients, 54 aneurysms) and medium aneurysms (18 patients, 23 aneurysms). There were 19 patients with tandem aneurysms (a total of 39 aneurysms) in the two groups, among which 15 patients (30 aneurysms) were in the small aneurysm group and four patients (nine aneurysms) were in the medium aneurysm group. The results show that the mean maximal diameter/neck in the small and medium aneurysms was 3.68/3.25 and 7.61/6.24 mm, respectively. In total, 57 Tubridge flow diverters were successfully implanted without unfolding failure, and there were six patients with new mild cerebral infarction in the small aneurysm group. The complete occlusion rate on the last angiographic follow-up was achieved in 88.46% of the small aneurysms group and 81.82% of the medium aneurysms group. The complete occlusion rate of patients with tandem aneurysms in the last angiographic follow-up was 86.67% (13/15) of the small aneurysms group and 50% (2/4) of the medium aneurysm group. Intracranial hemorrhage was nonencountered in the two groups. Conclusion Our preliminary experience suggests that the Tubridge flow diverter might be a safe and effective treatment for small and medium aneurysms along the internal carotid artery. Long stents may increase the risk of cerebral infarction. Adequate evidence is required to clarify the definite indications and complications in a multicenter randomized controlled trial with a long-term follow-up.